Pengaruh Penerapan Green Accounting Terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening - Astari Dianty (JURNAL EKBIS, 2022)
The condition of the value of the mining sub-sector companies in 2018 – 2020 decreased due to the decline in the financial performance of the mining sub-sector companies. This is indicated to occur because there are still many mining companies that have not implemented the concept of green accounting in their mining activities, thus affecting consumer perceptions when product sales occur. This study aims to analyze the effect of implementing green accounting on firm value with financial performance as an intervening variable. Data is obtained from 42 financial statements of companies in the mining sub-sector listed on the Indonesia Stock Exchange for the period 2018 - 2020. Green Accounting is measured using a Dummy Variable where the value is 0 for companies that do not have an environmental cost component and 1 for companies that have an environmental cost component. Finance is measured using Return on Assets and Firm Value is measured using Price to Book Value. Path analysis is used to analyze the effect of independent variables on the dependent variable, as well as the indirect effect of the intervening variable.